Bioatividade: uma propriedade secundária em vidros bioativos de composições complexas? - Santana, Lucas de Araújo Bastos (2021)
The test used to assess the bioactivity proposed by Kokubo associates the apatite formation on biomaterials immersed in simulated body fluid (SBF) with a better biological performance. However, there is evidence that some materials tend to stimulate osteoprogenitor cells regardless of apatite precipitation, i.e., in absence of bioactivity, especially in bioceramics with complex compositions. For instance, divalent ions such as Zn2+, Mg2+ and Mn2+ are known to play important roles in signaling cascades associated with bone regeneration, although they are known to diminish apatite precipitation under certain conditions. To further discuss the validity of Kokubo assays in predicting the biological performance of complex composition bioceramics, five different glass compositions were synthesized in which CaO was partially replaced by ZnO, MgO and MnO: 80% SiO2 · (16% - x) CaO · x% MO · 4% P2O5 (mol%; x = 0, 2 and 6%). The glasses were synthesized via the sol-gel process and their physical-chemical properties were evaluated by thermogravimetric analysis (TGA/DTG), differential thermal analysis (DTA), wavelengthdispersive X-ray fluorescence (WDXRF), Raman spectroscopy, X-ray diffraction (XRD), scanning electron microscopy (SEM) and surface roughness. The biological behavior of the glasses was studied via acellular bioactivity assay in SBF, followed by adhesion, proliferation and differentiation of osteoblast-like human osteosarcoma cells (MG-63). It was possible to observe that the mass loss events did not undergo significant changes after the partial replacement of CaO by MnO, ZnO and MgO oxides. However, the addition of oxides reduced the glass transition temperature (Tg) and the crystallization temperature (Tc) of the glasses due to the increase in non-binding oxygen (NBO). The glasses in which CaO was replaced had their bioactivity impaired, evidenced by the absence of formation of the hydroxyapatite surface layer in SBF. However, even with the inhibited bioactivity, the glass containing MgO was able to stimulate the adhesion, cell proliferation and ALP production of MG-63 cells. In glasses containing ZnO and MnO, bioactivity was also inhibited, while low cell proliferation and high production of ALP were observed. These results demonstrate a divergence between the expected biological performance suggested by Kokubo assay and the performance observed indeed from cellular assays with MG-63. Therefore, the presence of trace elements in bioceramics with complex compositions exposes even more the reliability of Kokubo assays in predicting their biological performance, notably adhesion, proliferation, and differentiation of osteoblastic cells, indicating that apatite formation is not a definitive criterion to confirm biocompatibility.